From Reactive to Proactive Governance: A Hybrid LSTM–Gradient Boosting Architecture for Real-Time Anomaly Signal Detection in Multi-Store Retail Supply Chain Decision Systems (Al-Farooq Journal of Sciences, 2026)
Contemporary multi-store retail supply chains operate under intensifying volatility driven by promotional dynamics, macroeconomic shocks, and exogenous disruptions yet most decision-support systems remain anchored in reactive, lagging indicators. This study introduces a novel hybrid deep learning architecture that synergistically integrates Long Short-Term Memory (LSTM) networks for temporal dependency modeling with Gradient Boosting Machines (GBM) for high-dimensional feature interaction capture, enabling real-time detection of latent risk signals within store-level sales trajectories. Leveraging the publicly available Store Sales  Time Series Forecasting dataset (Kaggle, 2022), comprising 54 Ecuadorian retail outlets, 3,000+ product families, and auxiliary covariates including oil prices, national holidays, and promotional intensity, we demonstrate that our stacked ensemble framework achieves superior early-warning capability compared to standalone LSTM, XGBoost, or ARIMA benchmarks. Critically, the architecture embeds a probabilistic calibration layer (Platt scaling) and SHAP-based interpretability module, transforming opaque risk scores into actionable procurement narratives for supply chain managers. Results indicate a 23.7% reduction in false-negative anomaly detection and a 15.2% improvement in lead-time for intervention signals, advancing the paradigm from post-hoc correction to anticipatory governance. The methodological contribution lies not merely in predictive accuracy, but in establishing a reproducible, auditable framework for embedding AI-driven risk intelligence within operational decision loops addressing the accountability, drift, and escalation gaps identified in contemporary autonomous supply chain .
Keywords: supply chain risk governance, hybrid deep learning, LSTM, gradient boosting, real-time anomaly detection, retail time-series forecasting, interpretable AI, proactive decision systems.